2013
DOI: 10.1021/mp4005723
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Atomic-Level Interaction between Mefenamic Acid and Eudragit EPO in a Supersaturated Solution by High-Resolution Magic-Angle Spinning NMR Spectroscopy

Abstract: The intermolecular interaction between mefenamic acid (MFA), a poorly water-soluble non-steroidal anti-inflammatory drug, and Eudragit® EPO (EPO), a water-soluble polymer, is investigated in their supersaturated solution using high-resolution magic-angle spinning (HRMAS) nuclear magnetic resonance (NMR) spectroscopy. The stable supersaturated solution with a high MFA concentration of 3.0 mg/mL is prepared by dispersing the amorphous solid dispersion into a d-acetate buffer at pH 5.5 and 37 °C. By virtue of MAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 42 publications
2
56
0
Order By: Relevance
“…Recently, 1 H-NMR spectroscopy was used to observe interactions between drugs and EUD-E in solution. [45][46][47][48] Our group has investigated drug-EUD-E interactions in detail using various 1 H-NMR techniques. 33,49) Kojima et al prepared a solid dispersion of mefenamic acid (MFA) and EUD-E at a weight ratio of 24 : 76 by cryogenic cogrinding.…”
Section: Direct Observation Of Drug-eud-e Interactions In Aqueous Solmentioning
confidence: 99%
“…Recently, 1 H-NMR spectroscopy was used to observe interactions between drugs and EUD-E in solution. [45][46][47][48] Our group has investigated drug-EUD-E interactions in detail using various 1 H-NMR techniques. 33,49) Kojima et al prepared a solid dispersion of mefenamic acid (MFA) and EUD-E at a weight ratio of 24 : 76 by cryogenic cogrinding.…”
Section: Direct Observation Of Drug-eud-e Interactions In Aqueous Solmentioning
confidence: 99%
“…Solid dispersion with EPO also improved the dissolution of indomethacin and piroxicam in weakly acidic solutions. Recently, we characterized MFA/EPO supersaturated solutions using high‐resolution magic‐angle spinning NMR, and the intermolecular interactions between MFA and EPO were clearly demonstrated using two‐dimensional NMR techniques such as nuclear Overhauser effect spectroscopy and radio frequency‐driven recoupling spectroscopy [22]. We also observed that the formation of ionic bonds and hydrogen bonds in addition to hydrophobic interactions between MFA and EPO could increase the stability of the supersaturated solution.…”
Section: Introductionmentioning
confidence: 86%
“…The same can be attributed to the flexible chains present in the polymer which accommodate themselves to form a clear matrix at a temperature as low as 40-45°C. This property, in particular, has been imparted by the low glass transition temperature (Tg of around 45°C) of Eudragit EPO (Higashi et al, 2014). As only Eudragit EPO was able to form a transparent film, the same was selected for further optimization employing DoE.…”
Section: In Vivo Pharmacokinetic Studiesmentioning
confidence: 99%
“…Further, Eudrgait EPO prevents the recrystallization by stabilizing the drug substance through hydrogen bonding, vander Waal and ionic interactions (Higashi et al, 2014). Povidone, on the other hand, provided a synergistic effect in drug release.…”
Section: In Vivo Pharmacokinetic Studiesmentioning
confidence: 99%